Evaluation of Pregnancy consequences in Women with Polycystic Ovary Syndrome: A Case-Control Study in Qazvin, Iran - Hamideh Pakniat; Fatemeh Kazemi; Farideh Movahed; Abotorabi Shokohossadat; Nasrin Soofizadeh; Farnaz Yaghoobi (مجله علمی دانشگاه علوم پزشکی کردستان, 2022)
Background and Aim: Polycystic ovary syndrome (PCOS) is a common disorder in women of childbearing age that can be associated with adverse pregnancy complications. The aim of this study was to compare the adverse pregnancy consequences between pregnant women with PCOS and control group in Qazvin. Materials and Methods: In this study, 150 pregnant women with PCOS aged 18-35 years with gestational age of more than 20 weeks were selected as our case group based on Rotterdam criteria and our control group included 150 pregnant women without PCOS. The groups were compared in terms of pregnancy complications including gestational diabetes, preeclampsia, preterm delivery, low birth weight, and neonatal admission to the neonatal intensive care unit (NICU). Results: There were no significant differences between the two groups in terms of demographic data including age, weight, height and BMI. In the case group (PCOS) we found gestational diabetes in 33 cases (64.7%) (P=0.021), preeclampsia in 44 cases (67.7%) (P=0.002), and preterm delivery 70 in cases (75.3%) which indicated a significant difference between the case and control groups (P<0.0001). The case group had higher neonatal complications than control group in regard to low birth weight (40 cases, 64.5%, P=0.008) and NICU admission (30 cases, 66.7%, P=0.015). Conclusion: The results of this study showed that PCOS, due to its metabolic effects, may increase the incidence of gestational diabetes, preeclampsia, preterm delivery, low birth weight or macrosomia and long term NICU admission